Pengembangan Sistem Pakar Untuk Diagnosis Penyakit Hepatitis Berbasis Web Menggunakan Metode Certainty Factor - Ahmad Ramdhani; R. Rizal Isnanto; Ike Pertiwi Windasari (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2015)
Expert System is a computer technology that can help people solving problems which are mostly applied in medicine. Expert System is system that trying to adopt human knowledge to the computer, so the computer can resolve the issue as done by an expert.. In this study, an Expert System to diagnose hepatitis disease consisting of Hepatitis A, Hepatitis B, and Hepatitis C will be created. This expert system to diagnose hepatitis disease is created using PHP programing language and MySQL database using Certainty Factor method. This expert system will ask for an input such as symtomps and blood test, then the result is the possibility of the disease suffered by the patient and an explanation of the disease and its treatment solution. This expert system is able to issue diagnosis results for Hepatitis A, Hepatitis B, and Hepatitis C.. Certainty Factor method can be applied to expert systems with simple disease or not complex, such as acute hepatitis disease that is done in this study.